Respuesta :
2x+3y=45
x+y=10
Take the bottom equation and solve for y
x+y=10
Subtract x from both sides
y=-x+10
Substitute into the top equation
2x+3(-x+10)=45
2x-3x+30=45
Subtract 30 from both sides + add like terms
-x=15
Divide both sides by -1
x=-15
x+y=10
Take the bottom equation and solve for y
x+y=10
Subtract x from both sides
y=-x+10
Substitute into the top equation
2x+3(-x+10)=45
2x-3x+30=45
Subtract 30 from both sides + add like terms
-x=15
Divide both sides by -1
x=-15
[tex]\begin{cases}&2x + 3y = 45 ----- (1) \\&x + y = 10 ----- (2) \end{cases}[/tex]
Make x the subject for equation (2):
[tex]\begin{cases}&2x + 3y = 45 ----- (1) \\&x = 10 - y ----- (2) \end{cases}[/tex]
Substitute equation (2) into equation (1):
[tex]2(10-y) + 3y = 45 [/tex]
[tex]20 -2y + 3y = 45 [/tex]
[tex]20 + y = 45 [/tex]
[tex]y = 45 - 20[/tex]
[tex]y = 25[/tex]
Subsitute y = 25 into equation (2):
[tex]x = 10 - (25)[/tex]
[tex]x = -15[/tex]
Answer: x = -15
Make x the subject for equation (2):
[tex]\begin{cases}&2x + 3y = 45 ----- (1) \\&x = 10 - y ----- (2) \end{cases}[/tex]
Substitute equation (2) into equation (1):
[tex]2(10-y) + 3y = 45 [/tex]
[tex]20 -2y + 3y = 45 [/tex]
[tex]20 + y = 45 [/tex]
[tex]y = 45 - 20[/tex]
[tex]y = 25[/tex]
Subsitute y = 25 into equation (2):
[tex]x = 10 - (25)[/tex]
[tex]x = -15[/tex]
Answer: x = -15